Innovative modified hair follicle harvesting technique with reverse rake scalp elevator for lower occipital donor area in follicular unit extraction hair transplantation - Chandrakant Rambhau Gharwade (Indian Journal of Plastic Surgery)
Follicular unit extraction (FUE) is one of the widely practiced minimally invasive follicular harvesting techniques employed during hair transplantation. FUE technique has an advantage of utilising lower occipital area and supra-auricular region as a safe donor area described by Unger, in addition to the standard occipital donor area used in strip method (follicular unit transplant). Despite its potential advantages such as rapid recovery, minimal scarring and reduced post-operative pain; its widespread acceptance is limited due to various factors in variable contribution like steeper learning curve and potentially higher follicular transection rates (FTRs). The main practical drawbacks in harvesting FUE from lower occipital donor region that lie inferior to the standard donor area, is its acute angle (10°–15°) of emergent hair from scalp skin, higher variance angle (15°–35°) between hairs below the skin and hair exit angle above the skin and comparatively loose scalp, preventing to provide stable platform for punching. Hair transplant surgeon faces difficulty in aligning and engaging the FUE punch leading to very high hair follicle transection rate, and therefore, it is not a preferred site for harvesting follicles in FUE. Authors description of modified technique using reverse rake scalp elevator helps in negating the acute angle of the hair follicles exit from scalp skin and reducing the variance angle between emergent hair and hair below the skin in lower occipital region thereby reducing FTR. Furthermore, an added advantage of reducing the overall operative time and surgeon fatigue, improve donor area healing, availability of a comparatively larger donor area which increases the confidence of the beginners. This method will be of help as it is easy to duplicate and follow by novice hair transplant surgeons and also for those who are routinely doing mega hair transplants sessions.